2016
DOI: 10.1194/jlr.p068015
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between non-HDL cholesterol and macrophage phenotypes in human adipose tissue

Abstract: Data from experimental animal models and in vitro studies suggest that both hyperlipoproteinemia and obesity predispose to development of proinflammatory pathways of macrophages within adipose tissue. The aim of this study was to analyze whether non-HDL cholesterol concentration in healthy living kidney donors (LKDs) is related to the number and phenotype of proinflammatory macrophages in visceral and subcutaneous adipose tissue. Adipose tissue samples were collected by cleansing the kidney grafts of LKDs obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 29 publications
0
17
0
3
Order By: Relevance
“…Obesity and obesity-related metabolic disorders are associated with elevated plasma TG levels, high low-density lipoprotein (LDL)-Chol and low high-density lipoprotein (HDL)-Chol contents, with non-HDL levels positively associated with pro-inflammatory ATMs even in healthy subjects [38,39]. Within blood vessel, TG is transported in the form of lipoproteins, including VLDL, which can bind to the VLDL receptor (VLDLR) at the surface of adipocytes and macrophages for TG uptake [40,41].…”
Section: Vldl/vldlrmentioning
confidence: 99%
“…Obesity and obesity-related metabolic disorders are associated with elevated plasma TG levels, high low-density lipoprotein (LDL)-Chol and low high-density lipoprotein (HDL)-Chol contents, with non-HDL levels positively associated with pro-inflammatory ATMs even in healthy subjects [38,39]. Within blood vessel, TG is transported in the form of lipoproteins, including VLDL, which can bind to the VLDL receptor (VLDLR) at the surface of adipocytes and macrophages for TG uptake [40,41].…”
Section: Vldl/vldlrmentioning
confidence: 99%
“…Several molecular mechanisms of the role of macrophages during the long-term process of atherogenesis have been elucidated [8]. We recently showed that the proportion of metabolically normally stimulated macrophages in human adipose tissue is positively related to body mass index (BMI) [9], age (differently in men and women) [10], and is very closely positively related to non-high-density lipoprotein HDL) cholesterol concentration [11]. On the other hand, the properties and behavior of normally stimulated proinflammatory macrophages in adipose tissue (referred to as M1) are not yet fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the properties and behavior of normally stimulated proinflammatory macrophages in adipose tissue (referred to as M1) are not yet fully understood. The common cause of the very close correlation of proatherogenic lipoprotein concentrations to polarization of adipose tissue macrophages [11] might be due to the mutual effect of diet on both parameters. Next, fatty acids (FAs) in phospholipids of adipose tissue cell membranes (probably the best parameter to document long-term saturated and unsaturated FA consumption) were analyzed and correlated to the proportion of proinflammatory adipose tissue macrophages.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested in a recent study that non-HDL-C may be superior to CRP in determining future cardiovascular events in children and adolescents with type 1 diabetes [32]. In fact, one study has shown that non-HDL-C has a high correlation with proin ammatory macrophages in adipose tissue [33]. Moreover, in an experimental study on apolipoprotein E-de cient mice, non-HDL-C reduction was reported to have a positive effect on the development of atherosclerosis by inhibiting leucocyte transmigration [34].…”
Section: Discussionmentioning
confidence: 99%